State regulation of the military economy - Shahob, Mokhtar (Journal of the Belarusian State University. Economics, 2018)
The problems of the military economy are covered, including the terms. The emphasis is on the role of the state in the military economy, the volumes of its effective financing, interaction with the private sector. The review of foreign experience in the field of management of the military budget and recommendations on the organization of partnership of the state, science and military business are given.
Keywords: military economy; defense budget; state interaction; partnership with business